A novel sperm adaptation to evolutionary constraints on reproduction: Pre‐ejaculatory sperm activation in the beach spawning capelin (Osmeridae). Issue 4 (29th January 2018) - Beirão, José; Lewis, Jason A.; Wringe, Brendan F.; Purchase, Craig F.
Abstract: Reproduction of external fertilizing vertebrates is typically constrained to either fresh or salt water, not both. For all studied amphibians and fishes, this constraint includes immotile sperm that are activated after ejaculation only by the specific chemistry of the fertilizing medium in which the species evolved (fresh, brackish, or salt water). No amphibians can reproduce in the sea. Although diadromous fishes may migrate between salt and fresh water, they are shackled to their natal environment for spawning in part because of sperm activation. Here, we report for the first time among all documented external fertilizing vertebrates, that in the absence of any external media, sperm are motile at ejaculation in a marine spawning fish (Osmeridae, capelin, Mallotus villosus ). To illuminate why, we evaluated sperm behavior at different salinities in M. villosus as well as the related freshwater spawning anadromous rainbow smelt ( Osmerus mordax ). Surprisingly, sperm performance was superior in fresh water for both species. M. villosus spend their entire life at sea but our results show that their sperm are deactivated by sea water, suggesting a freshwater ancestry. By circumventing constraining water chemistry, we interpret the unique pre‐ejaculatory sperm activation in this species as a novel adaptation that enables fertilization in the marine environment. These findings also contribute to understanding the persistence of anadromy, despite great energetic costs to adult fishes. Abstract : External fertilizing vertebrates are constrained in where they can reproduce by sperm biology. Here, we report a unique observation concerning sperm activation and hypothesize that it is a novel adaptation to allow a freshwater taxon to spawn in the sea.